Demand for Souvenirs During Covid-19 in Ambon City (UD.N. Case Study) - Lawalata, Marfin; Alzagladi, Nadirah; F. W. Thenu, Stephen (Journal of World Science, 2023)
The COVID-19 pandemic has brought unprecedented challenges to businesses worldwide, with the tourism industry being particularly hard-hit. In Ambon City, where tourism plays a significant role in the local economy, understanding the dynamics of souvenir demand during this crisis is crucial for the survival and adaptation of souvenir businesses like UD.N. This study was aimed at determining the Demand for souvenirs in UD. N. Ambon City. We conducted a mixed-methods research approach. First, surveys were administered to tourists or customers Ambon City to gather quantitative data on souvenir demand and preferences. Second, in-depth interviews were conducted with UD.N. owners and staff to gain insights into their strategies and challenges during the pandemic. Data analysis involved both descriptive statistics and thematic content analysis. Primary data was collected by interviewing as many as 40 people. Our findings reveal a significant decline in souvenir demand during the COVID-19 pandemic, primarily due to reduced tourism activities and travel restrictions. The results showed that the Demand for food souvenirs was significantly influenced by the price of souvenirs, consumer income, prices of substitute goods, age, tastes, and future forecasts simultaneously. Meanwhile, tastes and future forecasts partially influence the Demand for food souvenirs. On the other hand, the Demand for non-food souvenirs, simultaneously or partially, is not significantly influenced by all research variables. The types of food souvenirs that consumers are most interested in are sago tumbu and Nona Fitria Nut Bagea. Meanwhile, the most popular type of non-food souvenir is Namlea eucalyptus oil in 100 ml.